Fiduciary Principle in Maintaining Islamic Banking Customer's Loyalty amidst the Covid-19 Pandemic - Supriadi Supriadi; Samsul Samsul; Trisno Wardy Putra; Trimulato Trimulato; Muhlis Muhlis; Farid Fajrin; Nur Isra Ahmad (Al-Azhar Journal of Islamic Economics, 2021)
Islamic banks as intermediary institutions shall maintain and comply with sharia principles so that in carrying out their business, they will continue to gain trust from the community, especially during the Covid-19 pandemic. The principle that is highly fundamental for the existence of an industry including sharia banks is fiduciary principle. The purpose of this study was to examine the implementation of the fiduciary principle in maintaining customer loyalty amid the Covid-19 pandemic. The research method used in this study was descriptive analysis. The type of data used was secondary data, namely in the form of articles, magazines, research journals, books, and other sources relevant to this study. The data collection technique used was documentation technique. The results of the study showed that the trust given to customers by sharia banks can increase customer loyalty in conducting various transactions. In addition, various efforts also needed to be made by sharia banks in order to maintain customer loyalty in the midst of the current pandemic by improving service quality and maintaining customer perceptions regarding the image of the bank. Therefore, sharia banks must uphold this fiduciary principle in order to prevent banking risks that may occur amidst the COVID-19 pandemic.